Chile food power: Success or failure of a policy? - Mesa-Mesina, Francisco; Espinoza-Tellez, Teófilo; Quevedo-León, Roberto (Journal of the University of Zulia, 2022)
Chile implemented in 2006 a public-private policy called: Chile Food Power. The policy was aimed at positioning Chile as a global food export power. The present work is an exploratory, descriptive and longitudinal analysis research. The information was collected through a content file that included: author, year, research area, phrase or paragraph, page number, title, place, edition, editorial, source, web. The information was obtained from: academic databases, the internet and social media, which were validated with official information from the Chilean government and international organizations. The work concludes that Chile's food exports in FOB amounts: fruits and vegetables, fish and shellfish, and alcoholic beverages have had a linear economic growth of 275% between the period 2002 to 2018 and continue to grow. Finally, we can say that the Chile Food Power Policy was a success in value- added food exports, despite how competitive world food markets are and how difficult it is to access to them.